DAMPAK KEBERADAAN INDUSTRI NIKEL TERHADAP ASPEK SOSIAL, EKONOMI DAN LINGKUNGAN DALAM MENDUKUNG KEBERLANJUTAN USAHATANI PADI SAWAH DI DESA PAKU JAYA KABUPATEN KONAWE - Risky Awaliah; Iskandar Zainuddin Rela; Salahuddin; Darsilan Dima (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
This study aims to determine the impact of the nickel industry on social, economic, and environmental aspects in supporting the sustainability of rice farming. The study was conducted in Paku Jaya Village, Morosi District, Konawe Regency, from November to January 2024, with 15 informants. This study employs a qualitative method, with data collection through observation, in-depth interviews, and literature review. Data analysis utilizes the interactive model by Miles, Huberman, and Saldana. The objects of this study were the impacts of the nickel industry on social aspects, namely family education, agricultural technology adaptation, and farmer participation. The impacts on economic aspects were farmers' income, alternative employment opportunities, and farming productivity. Environmental aspects included irrigation water quality, air pollution, and ecosystem damage. The results of the study found that the presence of the nickel industry had a significant impact on the social, economic, and environmental aspects of rice farmers. The social impacts of the company's presence include job transitions, decreased motivation for education, and low farmer participation in sustainable agriculture programs. The economic impacts include decreased income, limited alternative employment opportunities, and reduced agricultural productivity. The environmental impacts include decreased irrigation water quality, air pollution, and ecosystem damage. The presence of the nickel industry as a whole does not support the sustainability of rice farming.